The formation and evolution of Titan’s winter polar vortex - Nicholas A. Teanby (Nature Portfolio, 2017)
The polar hot-spot appeared in Titan after equinox in 2010 suddenly cooled in early 2012, which wasn’t predicted by models. Here the authors use observations to show that the increase in trace gases during the hot-spot resulted in radiative cooling feedback.